A New Supply Chain System and Its Impulsive Synchronization. (13th October 2020) - Peng, Yang; Wu, Jiang; Wen, Shiping; Feng, Yuming; Tu, Zhengwen; Zou, Limin
Abstract : The purpose of this paper is to discuss modelling and synchronization of nonlinear supply chain system. Firstly, we present a new supply chain system which is sensitive to various uncertainties along with exogenous disturbances. Synchronization is an important method to reduce the negative impact of uncertainties and disturbances on the supply chain. Since impulsive control can reduce control cost and the amount of transmitted information drastically, we discuss impulsive synchronization behavior of two supply chain systems with the same structure. Finally, simulation experiments are given to show the effectiveness of our analytical results.